Homogenization in elastic random media - Kamiński, Marcin (Computer Assisted Methods in Engineering and Science, 1996)
The theoretical foundation and a numerical procedure of deriving stochastic effective properties of linear-elastic periodic fibre composite are presented. Using Monte-Carlo method, a Fortran program based on the deterministic rectangular plane strain element of the Finite Element Method has been worked out to evaluate probabilistic density functions of these properties. The expected values of elastic effective characteristics thus obtained are compared with deterministic results of COSAN modelling.